Mobile Application Sistem Monitoring Kegiatan Dan Keuangan Masjid - Yanni Suherman; Erien Nada Azandra; Ahmad Fikri Fajri; Khairil Hamdi; Ade Zevimarino (LPPM STIKOM Tunas Bangsa, 2022)
The information system currently used by the Mujahiddin Mosque is still manual with data recording still using books, so it is very vulnerable to data loss. Seeing from this situation, it is necessary to design an Android-based system application for the mosque. With this Android system, it facilitates and assists mosque administrators in carrying out daily activities in the mosque environment. The research method used is based on the stages in the system development method. The Android system to be built uses the JavaScript programming language. The contents of this system itself are about finances and activities at the Mujahiddin Mosque, both regarding prayer schedules, about mosque activities, mosque infaq data, and other report data so that they are more neatly organized. Thus, the existence of a financial management information system and mosque data activities at the Mujahiddin Mosque in Padang City can assist the mosque in carrying out its daily activities and activities so that it makes it easier for administrators to convey information to congregations, both in the form of activity and financial information. In addition, with this system there will be no more incidents of losing mosque data because it has been stored directly into the database system.